2020
DOI: 10.15562/ism.v11i1.632
|View full text |Cite
|
Sign up to set email alerts
|

Peningkatan kadar Mean Platelet Volume-Lymphocyte Ratio (MPVLR) terhadap resiko diabetik nefropati pada pasien dengan diabetes melitus tipe II (DM-2) di RSUP Sanglah, Bali, Indonesia

Abstract: Background: Diabetic Nephropathy (DN) is Diabetes Mellitus’s microvascular complication with albuminuria and decrease glomerular filtration rate. DN pathogenesis is related with inflammatory process induced by chronic hyperglycaemia. Mean platelet volume (MPV)  and platelet-lymphocyte ratio (PLR) are potential for reviewing systemic inflammation. The combination of MPV and PLR index into MPVLR shows significant results in prognostic patients with diabetes mellitus and acute myocardial infarction and predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…22 Inflammation in DKD involves the increase of oxidative stress in the kidney. 6,23,24 Several studies have found that ELMO1 cytokine plays an important role in the increase of oxidative stress 6 , although the specific mechanism that explains the role of SNP rs741301 polymorphism in ELMO1 gene in DKD is still unclear. In a series of studies, it is found that an increase in ELMO1 serum level causes Rac1 activation through the RhoG-ELMO-DOCK180 pathway complex, which increases the NOX and ROS 5,21 as well as fibronectin gene expression through COX-2 activity.…”
Section: Discussionmentioning
confidence: 99%
“…22 Inflammation in DKD involves the increase of oxidative stress in the kidney. 6,23,24 Several studies have found that ELMO1 cytokine plays an important role in the increase of oxidative stress 6 , although the specific mechanism that explains the role of SNP rs741301 polymorphism in ELMO1 gene in DKD is still unclear. In a series of studies, it is found that an increase in ELMO1 serum level causes Rac1 activation through the RhoG-ELMO-DOCK180 pathway complex, which increases the NOX and ROS 5,21 as well as fibronectin gene expression through COX-2 activity.…”
Section: Discussionmentioning
confidence: 99%